A Facile, Efficient and Selective Deprotection of P - Methoxy Benzyl Ethers Using Zinc (II) Trifluoromethanesulfonate - Sireesha, Reddymasu; Sreenivasulu, Reddymasu; Chandrasekhar, Choragudi; Rao, Mannam S. (Letters in Organic Chemistry, 2019)
Deprotection is significant and conducted over mild reaction conditions, in order to restrict any more side reactions with sensitive functional groups as well as racemization or epimerization of stereo center because the protective groups are often cleaved at last stage in the synthesis. P - Methoxy benzyl (PMB) ether appears unique due to its easy introduction and removal than the other benzyl ether protecting groups. A facile, efficient and highly selective cleavage of P - methoxy benzyl ethers was reported by using 20 mole% Zinc (II) Trifluoromethanesulfonate at room temperature in acetonitrile solvent over 15-120 min. time period. To study the generality of this methodology, several PMB ethers were prepared from a variety of substrates having different protecting groups and subjected to deprotection of PMB ethers using Zn(OTf)2 in acetonitrile. In this methodology, zinc triflate cleaves only PMB ethers without affecting acid sensitivity, base sensitivity and also chiral epoxide groups.
Keywords: selective deprotection